Peran Guru PAI dalam Membangun Karakter Disiplin dan Bertanggung Jawab Siswa Pascapandemi Covid-19 Di SMK Ma’arif 1 Kebumen - Astuti, Wiji; Rinawati, Atim (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
This study aims to determine the role of islamic religious education teachers in building the character of discipline and responsibility of students at SMK Ma’arif 1 Kebumen and find out what factors support and hinder the development of the character of discipline and responsibility of students at SMK Ma’arif 1 Kebumen Post- pandemic Covid-19. This research method is field research by looking at the problem studied through a qualitative approach. Collecting data using observation techniques, interviews and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results showed that the role of the teacher in building the character of discipline and responsibility of post-covid-19 students at SMK Ma’arif 1 Kebumen was good, namely through various roles such as the role of the teacher as a teacher, the teacher as a guide, and the teacher as a motivator. And methods for building the character of discipline and responsibility after the pandemic, such as exemplary methods, habituation and reforming the character of discipline and responsibility. While the supporting and inhibiting factors in building the character of discipline and student responsibility after the Covid-19 pandemic are the entire school, the culture of school habituation, and cooperation between teachers and parents, while the obstacles are student self-awareness, gadgets and the environment in which students live